Odpowiedź :
Odpowiedź:
[tex]4 \times ( - 0.2) \times ( - 0.25) = 4 \times 0.2 \times 0.25 = \\ 1 \times 0.2 = 0.2[/tex]
[tex] \frac{1}{2} \times ( - \frac{3}{4} ) \times 8 = - \frac{3}{4} \times 4 = - 3[/tex]
[tex]( - 8) \times ( - 1 \frac{1}{3} ) \times \frac{5}{4} \times ( - 0.1) = \\ ( - 8) \times ( - \frac{4}{3} ) \times \frac{5}{4} \times ( - \frac{1}{10} ) = \\ - 8 \times \frac{1}{3} \times \frac{1}{2} = - 4 \times \frac{1}{3} = - \frac{4}{3} [/tex]
[tex]8 \times ( - 0.7) \times ( - \frac{1}{2} ) \times 10 = \\ 8 \times ( - \frac{7}{10} ) \times ( - \frac{1}{2} ) \times 10 = \\ 8 \times 7 \times \frac{1}{2} = 4 \times 7 = 28[/tex]
[tex] - 5 \times \frac{2}{3} \times ( - 1.5) \times 0.2 = \\ - 5 \times \frac{2}{3} \times ( - \frac{3}{2} ) \times \frac{1}{5} = \frac{2}{3} \times \frac{3}{2} \times 1 = \\ \frac{1}{3} \times 3 \times 1 = 1[/tex]
[tex] - \frac{3}{7} \times \frac{5}{6} \times ( - 4.9) \times 20 = \\ - \frac{3}{7} \times \frac{5}{6} \times ( - \frac{49}{10} ) \times 20 = \\ \frac{5}{2} \times 7 \times 2 = 5 \times 7 = 35[/tex]